Capacitance spectroscopy of InAs quantum dots inserted in an AlGaAs/GaAs HEMT for photodetector applications - Abdelaali Fargi; Sami Ghedira; Adel Kalboussi (AIP Advances, 2023)
We have investigated the electrical characteristics of an AlGaAs/GaAs high electron mobility transistor, in which a layer of InAs self-assembled Quantum Dots (QDs) was inserted below the 2DEG channel. A Negative Differential Capacitance (NDC) appeared in the capacitance–voltage characteristics at a bias of 1 V and at low temperatures (even at room temperature) under different illumination powers using white light bulbs. This results in an increase in negative differential conductance with the increase in frequency and optical power. This also applies to the NDC except that it decreases with increasing frequency. The numerical simulation of the energy band structure of the device confirmed that the conduction band lowers to its minimum at a special bias value of 1 V. The numerical analysis of the evolution of the energy levels in the QD-HEMT follows the appearance of multiple capacitance peaks and their behavior with the gate voltage.